Quantitative proteomics characterization on the antitumor effects of isodeoxyelephantopin against nasopharyngeal carcinoma. Issue 21 (3rd October 2013) - Yan, Guang‐Rong; Tan, Zilu; Wang, Yang; Xu, Man‐Li; Yu, Guangchuang; Li, Yaolan; He, Qing‐Yu
<x xml:space="preserve">Abstract</x> Isolated from Elephantopus scaber L., a Chinese medicinal herb that is widely used to prevent and treat cancers in China, isodeoxyelephantopin (ESI) exerted antitumor effects on several cancer cells. However, its antitumor mechanism is still not clear. In this study, we found that ESI could induce G2/M arrest and subsequently stimulate cell apoptosis in dose‐ and time‐dependent manners. We used SILAC quantitative proteomics to identify ESI‐regulated proteins in cancer cells, and found that 124 proteins were significantly altered in expression. Gene ontology and Ingenuity Pathway Analysis revealed that these proteins were mainly involved in the regulation of oxidative stress and inflammation response. Functional studies demonstrated that ESI induced G2/M arrest and apoptosis by inducing ROS generation, and that antioxidant N‐acetyl‐l‐cysteine could block the ESI‐induced antitumor effects. Accumulated ROS resulted in DNA breakage, subsequent G2/M arrest and mitochondrial‐mediated apoptosis. ESI upregulated the expression of anticancer inflammation factors IL‐12a, IFN‐α, and IFN‐β through ROS‐dependent and independent pathways. The current work reveals that ESI exerts its antitumor effects through ROS‐dependent DNA damage, mitochondrial‐mediated apoptosis mechanism and antitumor inflammation factor pathway.